High school curricula and human capital in nineteenth and twentieth centuries Spain - Nuñez, Clara Eugenia (Historia y Memoria de la Educación, 2024)
During the nineteenth and early twentieth centuries, most European countries adopted a modern education system. Making comparisons across countries and throughout the centuries is difficult, however, as the number of years of schooling required to graduate and the curricula changed quite frequently. This paper defines a new unit of measure to evaluate curricular changes across time and place: hours per week by discipline needed to complete a secondary school degree. Using data from two different sources, we have estimated two Indexes in Spain which are then applied to enrolment rates. 1) A Legal High School based upon the curricular contents required to graduate and obtain the Bachiller degree according to Spanish educational laws; and 2) a Real or San Isidro Index, using annual calendar data from that Institute in Madrid to capture the actual implementation of those bills. Both refer to a previously defined Finnish 2010 Standard built on one of the best-known protocols. We assume that the closer they were to the Finnish Standard, the better the Spanish school curricula were. Both indexes have been used to estimate a quality-adjusted and long-term consistent measure –a constant as against a current value– of the number of high school students from which measures of the stock of human capital, such as average years of schooling, are usually estimated. The new series are an improvement upon previously available indicators of human capital stock in the long-term and might prove useful for future studies regarding its impact upon the modernization of the country.